When 14C Dates Fall Beyond the Limits of Uncertainty: An Assessment of Anomalies in Western Mediterranean Bronze Age 14C Series. Issue 5 (2015) - Lull, Vicente; Micó, Rafael; Rihuete-Herrada, Cristina; Risch, Roberto
Abstract : The aim of this article is to bring to light a serious problem affecting radiocarbon dates produced at least from 2009 onwards by the AMS Leibniz laboratory at the Christian-Albrechts-Universität (Kiel, Germany). Archaeological observations and cross-checkings between several laboratories confirm that in a significant number of dates, clear deviations of the results from chronological schemes based on stratigraphical sequences and hundreds of measurements have occurred, which usually implies an aging of the 14 C values.